Rnd3 deletion affects neuroblast behavior through the RhoA/ROCK pathway but not neural stem cells in postnatal mice subventricular zone - Amalia Solana-Orts; Germán Belenguer; Germán Belenguer; Germán Belenguer; Begoña Ballester-Lurbe; Olga Gómez; Ignacio Pérez-Roger; José Terrado; Enric Poch; Alexandra Bizy (Frontiers in Cell and Developmental Biology)
In the subventricular zone (SVZ), neural stem cells (NSCs) generate neural progenitor cells (NPCs), which proliferate and differentiate into neuroblasts (NBs) that will travel along the rostral migratory stream (RMS) to the olfactory bulbs (OBs), where they mature into interneurons. Rnd3, a member of the Rho GTPase family, regulates cytoskeletal dynamics, neuronal morphology, and survival, primarily by interacting with the RhoA/ROCK pathway. In the central nervous system, Rnd3 is highly expressed during early postnatal development and is essential for neural function, axonal myelination, and neuronal polarization, as its deficiency leads to severe motor and neurodevelopmental impairments. In this study we show that NBs from Rnd3 KO mice accumulate in the SVZ and that these are principally characterized as late/migrating NBs. We investigated whether the observed accumulation results from increased proliferation and/or differentiation potential of NSCs and NPCs, and/or altered NB migration to the OBs through the RMS, potentially accompanied by increased proliferation. Our in vitro experiments indicate that the loss of Rnd3 does not affect NSC behavior. In addition, RNA sequencing reveals that Rnd3 expression is highest in NBs, particularly in late-stage NBs, suggesting a potential role in migration. Furthermore, gene expression analyses indicate that the loss of Rnd3 may disrupt NB cytoskeletal dynamics by altering the expression of key components of the RhoA/ROCK signaling pathway. These findings provide mechanistic insights into how Rnd3 deletion impairs NB migration.